The global, regional, and national burden of pancreatic cancer and its attributable risk factors in 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017 - Pourshams, Akram; Sepanlou, Sadaf G.; Ikuta, Kevin S.; Bisignano, Catherine; Safiri, Saeid; Roshandel, Gholamreza; Sharif, Mehdi; Khatibian, Morteza; Fitzmaurice, Christina; Nixon, Molly R.; Abbasi, Nooshin; Afarideh, Mohsen; et al. (The Lancet Gastroenterology & Hepatology, 2019)
Pourshams A, Sepanlou SG, Ikuta KS, et al. The global, regional, and national burden of pancreatic cancer and its attributable risk factors in 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017. LANCET GASTROENTEROLOGY & HEPATOLOGY . 2019;4(12):934-947. Background Worldwide, both the incidence and death rates of pancreatic cancer are increasing. Evaluation of pancreatic cancer burden and its global, regional, and national patterns is crucial to policy making and better resource allocation for controlling pancreatic cancer risk factors, developing early detection methods, and providing faster and more effective treatments. Methods Vital registration, vital registration sample, and cancer registry data were used to generate mortality, incidence, and disability-adjusted life-years (DALYs) estimates. We used the comparative risk assessment framework to estimate the proportion of deaths attributable to risk factors for pancreatic cancer: smoking, high fasting plasma glucose, and high body-mass index. All of the estimates were reported as counts and age-standardised rates per 100 000 person-years. 95% uncertainty intervals (UIs) were reported for all estimates. Findings In 2017, there were 448 000 (95% UI 439 000-456 000) incident cases of pancreatic cancer globally, of which 232 000 (210 000-221 000; 51.9%) were in males. The age-standardised incidence rate was 5.0 (4.9-5.1) per 100 000 person-years in 1990 and increased to 5.7 (5.6-5.8) per 100 000 person-years in 2017. There was a 2.3 times increase in number of deaths for both sexes from 196 000 (193 000-200 000) in 1990 to 441 000 (433 000-449 000) in 2017. There was a 2.1 times increase in DALYs due to pancreatic cancer, increasing from 4.4 million (4.3-4.5) in 1990 to 9.1 million (8.9-9.3) in 2017. The age-standardised death rate of pancreatic cancer was highest in the high-income super-region across all years from 1990 to 2017. In 2017, the highest age-standardised death rates were observed in Greenland (17.4 [15.8-19.0] per 100 000 person-years) and Uruguay (12.1 [10.9-13.5] per 100 000 person-years). These countries also had the highest age-standardised death rates in 1990. Bangladesh (1.9 [1.5-2.3] per 100 000 person-years) had the lowest rate in 2017, and Sao Tome and Principe (1.3 [1.1-1.5] per 100 000 person-years) had the lowest rate in 1990. The numbers of incident cases and deaths peaked at the ages of 65-69 years for males and at 75-79 years for females. Age-standardised pancreatic cancer deaths worldwide were primarily attributable to smoking (21.1% [18.8-23.7]), high fasting plasma glucose (8.9% [2.1-19.4]), and high body-mass index (6.2% [2.5-11.4]) in 2017. Interpretation Globally, the number of deaths, incident cases, and DALYs caused by pancreatic cancer has more than doubled from 1990 to 2017. The increase in incidence of pancreatic cancer is likely to continue as the population ages. Prevention strategies should focus on modifiable risk factors. Development of screening programmes for early detection and more effective treatment strategies for pancreatic cancer are needed. Copyright (C) 2019 The Author(s). Published by Elsevier Ltd.